Insectivorous birds can see and smell systemically herbivore‐induced pines. Issue 17 (4th August 2020) - Mäntylä, Elina; Kipper, Silke; Hilker, Monika
Abstract: Several studies have shown that insectivorous birds are attracted to herbivore‐damaged trees even when they cannot see or smell the actual herbivores or their feces. However, it often remained an open question whether birds are attracted by herbivore‐induced changes in leaf odor or in leaf light reflectance or by both types of changes. Our study addressed this question by investigating the response of great tits ( Parus major ) and blue tits ( Cyanistes caeruleus ) to Scots pine ( Pinus sylvestris ) damaged by pine sawfly larvae ( Diprion pini ). We released the birds individually to a study booth, where they were simultaneously offered a systemically herbivore‐induced and a noninfested control pine branch. In the first experiment, the birds could see the branches, but could not smell them, because each branch was kept inside a transparent, airtight cylinder. In the second experiment, the birds could smell the branches, but could not see them, because each branch was placed inside a nontransparent cylinder with a mesh lid. The results show that the birds were more attracted to the herbivore‐induced branch in both experiments. Hence, either type of the tested cues, the herbivore‐induced visual plant cue alone as well as the olfactory cues per se, is attractive to the birds. Abstract : Both great tits and blue tits were attracted to systemically herbivore‐damaged pines when they could only see or only smell the experimental branches. This is the first ever study to show that both vision and olfaction alone are enough for attraction of insectivorous birds to herbivore‐damaged trees.